Equity, equality in health care : priorities in the allocation of technologically sophisticated and expensive health care resources - Nevhutalu, Helen Khanyisa (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Phil.) -- University of Stellenbosch, 1998.